2007
DOI: 10.1002/ptr.2234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sairei‐to on the pharmacokinetics of nifedipine in rats

Abstract: Sairei-to is a traditional herbal medicine used to complement, and as an alternative to, Western drugs. The aim of this study was to evaluate the pharmacokinetic interactions between Sairei-to and nifedipine (NFP), a substrate for CYP3A, in rats. NFP-oxidizing activity and the pharmacokinetics of NFP were examined after a single or 1-week of administration of Sairei-to (EK-114). NFP-oxidizing activity was enhanced transiently around 24 h after a single administration of EK-114 (1400 mg/kg). In vivo, the first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, a discrepant report in terms of Saireito (Kanebo Ltd.) on the pharmacokinetic of nifedipine in vivo has been published by Ikehata et al [17]. Although the values of C max and AUC for the control groups were higher than those reported by Ikehata, the values of F were almost the same.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, a discrepant report in terms of Saireito (Kanebo Ltd.) on the pharmacokinetic of nifedipine in vivo has been published by Ikehata et al [17]. Although the values of C max and AUC for the control groups were higher than those reported by Ikehata, the values of F were almost the same.…”
Section: Discussionmentioning
confidence: 87%
“…The high bioavailability is probably due to the avoidance of hepatic first-pass elimination 18) by CA absorbed from the rectum, and the lower contribution of metabolic enzymes and transporters in the intestine to the absorption of CA from the rectum. Further investigations are needed to clarify the absorption mechanism of CA upon rectal administration of goreisan suppository because intestinal absorption of CA in rats is reported to be affected by the metabolic enzyme CYP 3A4 19) and the transporter gp-1. 20) This result suggested that CA in goreisan suppository was rapidly absorbed rectally, implying the rapid onset of a medical effect.…”
Section: Discussionmentioning
confidence: 99%
“…Because Kampo medicines include many kinds of herbs, Kampo-western drug interaction mediated by this enzyme was anticipated. In fact, among a number of Kampo medicines the high dose of saireito was suggested to have the ability to enhance and inhibit the metabolism of nifedipine in rats (8); meanwhile, rikkunshito, yokukansan, and boiogito have minimal effect on the metabolism of triazolam in mice (9). However, these kinds of investigations are quite limited and there is no information concerning CYP3A-mediated drug interaction for most of the Kampo medicines, even for those that are used frequently.…”
Section: Introductionmentioning
confidence: 99%